2023
DOI: 10.1007/s12664-022-01334-4
|View full text |Cite
|
Sign up to set email alerts
|

Novel radiological technique to recognize acute liver failure caused by yellow phosphorous containing rodenticides

Abstract: Yellow phosphorous rodenticide (YPR) poisoning is the commonest cause for acute liver failure (ALF) in southern and western India. Due to medicolegal issues, history of YPR ingestion may not be available. As early recognition of YPR poisoning is important and there are no specific biochemical assays, other early predictors to identify this entity is necessary. We evaluated the diagnostic role of plain computed tomography (CT) in identifying YPR-induced ALF. All patients admitted to the liver unit with a diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
(7 reference statements)
0
0
0
Order By: Relevance
“…Gopal and colleagues from Vellore, India, looked at their data of patients with ALF to find out whether any parameter would help differentiate patients with different causes for ALF (yellow phosphorous poisoning [YPR; n = 13] vs. other causes for ALF [n = 11]) [14]. They found that the clinical and biochemical parameters were almost similar in both groups.…”
Section: Identifying the Cause For Rodenticides-infested Liver: Ct Sc...mentioning
confidence: 99%
“…Gopal and colleagues from Vellore, India, looked at their data of patients with ALF to find out whether any parameter would help differentiate patients with different causes for ALF (yellow phosphorous poisoning [YPR; n = 13] vs. other causes for ALF [n = 11]) [14]. They found that the clinical and biochemical parameters were almost similar in both groups.…”
Section: Identifying the Cause For Rodenticides-infested Liver: Ct Sc...mentioning
confidence: 99%